The Impact of DNA Extraction Methods on Stool Bacterial and Fungal Microbiota Community Recovery - Fiedorová, Kristýna; Radvanský, Matěj; Němcová, Eva; Grombiříková, Hana; Bosák, Juraj; Černochová, Michaela; Lexa, Matej; Šmajs, David; Freiberger, Tomáš (Frontiers in Microbiology, 2019)
Our understanding of human gut microbiota in health and disease depends on accurate and reproducible microbial data acquisition. The critical step in this process is to apply an appropriate methodology to extract microbial DNA, since biases introduced during the DNA extraction process may result in inaccurate microbial representation. In this study, we attempted to find a DNA extraction protocol which could be effectively used to analyze both the bacterial and fungal community. We evaluated the effect of five DNA extraction methods (QIAamp DNA Stool Mini Kit, PureLink™ Microbiome DNA Purification Kit, ZR Fecal DNA MiniPrep™ Kit, NucleoSpin® DNA Stool Kit, and IHMS protocol Q) on bacterial and fungal gut microbiome recovery using i) a defined system of germ-free mice feces spiked with bacterial or fungal strains, and ii) non-spiked human feces. In our experimental setup, we confirmed that the examined methods significantly differed in efficiency and quality, which affected the identified stool microbiome composition. In addition, our results indicated that fungal DNA extraction might be prone to be affected by reagent/kit contamination, and thus an appropriate blank control should be included in mycobiome research. Overall, standardized IHMS protocol Q, recommended by the International Human Microbiome Consortium, performed the best when considering all the parameters analyzed, and thus could be applied not only in bacterial, but also in fungal microbiome research.